PERLINDUNGAN HUKUM HAK KOMUNITAS MASYARAKAT ADAT (STUDI PERLINDUNGAN RIMBA LARANGAN MASYARAKAT ADAT RUMBIO KAMPAR - Sari, Dwi Mutia; ', Firdaus; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Customary law is part of the law which is derived from the customs, ie social rules that are created and maintained by the legal functionaries and intended to regulate legal relations in a society and have sanctions. The 1945 Constitution of Indonesia concerning on customary law has stipulated in Article 18B paragraph (2), the article states that